Post-graduation: vision of a group of students of master-EE/RP-USP - Ana Fátima Carvalho Fernandes; Silvana Martins Mishima; Marli Villela Mamede (Rev Rene)
The work objectifies to describe the meaning of the post-graduation/master- for a group of student of EE/RP-USP-1997. It is a study of descriptive nature, with a qualitative approach, in order to analyse the thinking of the masters degree students concerning the master. The meaning that emerged were: professional and personal growth, learning X improvement, looks for of the scientific investigation, interaction with other professional X knowledge, new directions X growth. It is ended that the master is being of highest importance in the these students’ life, where the learning takes the search of a good quality in the teaching and in the professional life.